Variable Sign-Sign Wilcoxon Algorithm: A Novel Approach for System Identification - Mihir Narayan Mohanty; Sidhartha Dash (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Behavioral study of a system is an important task. It is mostly used in real world environments and became an emergent research area. Various approaches have been proposed since last two decades. In this paper, we have proposed a Variable Step-Size Sign-Sign Wilcoxon Approach, that is robust against outliers in the desired data and also convergence speed is faster than Wilcoxon norm based approach. In initial stage, Sign-Sign Wilcoxon norm based approach has been verified. Next to it, the proposed approach is verified and compared for the application in Linear and Non-linear system identification problems in presence of outliers.DOI:http://dx.doi.org/10.11591/ijece.v2i4.837